Collective emotions, triggering events, and self-organization: the forest-fire model of cultural identity conflict escalation - Schulte, Felix; Trinn, Christoph (Aggression and violent behavior, 2014)
Ethnic and religious conflicts frequently evolve into highly explosive situations marked by the sudden eruption of conflictive mass behaviour in the form of leaderless protests or riots. In this article, we introduce a new theoretical approach, the forest-fire model of cultural identity conflict escalation (FFM). The model offers a fresh perspective on conflict dynamics by focusing on the nonlinear dynamics inherent in self-organized collective mass behaviour in ethnic and religious conflicts. It serves to overcome the dominance of rationalist elite-centred and structuralist-institutionalist approaches in the field. We conceptualize conflictive mass behaviour as avalanching “cascades” to facilitate an understanding of the complex dynamics of ethnic and religious upheavals. The FFM unites time-invariant antecedent conditions of conflictive mass behaviour with extremely time-variant triggering events. According to the model, an emboldening emotional climate, characterized by a blend of shared anger, pride and hope, provides the “fuel” that is sparked by a disruptive incident. By integrating collective emotions, triggering events, and leaderless self-organization, the model offers an innovative and substantiated elucidation of the nonlinear, short-term escalation dynamics of collective mass behaviour in cultural identity conflicts.